Toward a generalized theory of the shift to retrieval in cognitive skill learning. - Bajic, Daniel; Rickard, Timothy (Memory & Cognition, 2011)
Prior research on cognitive skill learning has shown that algorithmic and direct memory retrieval strategies are not executed in parallel if the algorithm entails a series of long-term memory (LTM) retrieval steps (as in the case, for example, of mental arithmetic). This phenomenon has been hypothesized to reflect a bottleneck in LTM retrieval processes that forces a strategy choice during an early stage of processing. Here, we investigate simple perceptual-motor algorithms that involve no memory retrieval steps, a largely unexplored case in which parallel strategy execution models remain viable. Pronounced strategy interference was again observed, albeit interference that was different in important respects from that observed for LTM retrieval algorithms. It appears that neither parallel nor choice models, as developed to date, are sufficient as a generalized theory of this skill learning phenomenon. Issues central to the development of a more comprehensive theory are discussed.